Effect of Ionospheric Scintillation on Precise Positioning Solutions in Vietnam - Hiep, Hoang Van; Tien, Nguyen Duc; Vinh, La The (Old Journal, 2019)
The relative positioning applications can reach cm-level accuracy of positioning due to the use the very precise but ambiguous carrier phase observations instead of pseudorange ones used in conventional absolute positioning approach. These applications, however, are very sensitive to the irregular variation and disturbances in the ionospheric delay. Vietnam locates at a low-latitude region near the equator where having many irregular variations in ionosphere. In addition, Ionosphere is one of the most affected region if any scintillation occurs. In this study, we first propose a software-based receiver to detect the ionospheric scintillation in Vietnam. After detecting the scintillation, we investigate the impact of the scintillation index to the precise positioning solutions. For scintillation detection, we compute ΦΦp, a parameter to quantify the scintillation index. To investigate the effect of scintillation, we compare the results of RTK solutions in two scenarios: no scintillation and scintillation. Hopefully, these results will contribute valued information to GNSS research community in Vietnam.